Structural based insights into the role of troponin in cardiac muscle pathophysiology - Li, Monica X.; Wang, Xu; Sykes, Brian D. (Journal of muscle research and cell motility, 2004)
Troponin is a molecular switch, directly regulating the Ca2+-dependent activation of myofilament in striated muscle contraction. Cardiac troponin is subject to covalent and noncovalent modifications; phosphorylation modulates myofilament physiology, mutations are linked to familial hypertrophic cardiomyopathy, intracellular acidification causes myocardial infarction, and cardiotonic drugs modify myofilament response to Ca2+. The structure of troponin provides insights into the mechanism of this molecular switch and an understanding of the effects of protein modification under pathophysiological conditions. Although the structure of troponin C has been solved in various Ca2+-bound states for some time, structural information on troponin I and troponin T has only emerged recently. This review summarizes recent advances on the structure of complexes of troponin subunits with the aim of assessing how these proteins interact with each other to execute its role as a molecular switch and how covalent and noncovalent modifications affect the structure of troponin and the switch mechanism. We focus on pinpointing the specific amino acid residues involved in phosphorylation and mutation and the pH sensitive regions in the structure of troponin. We also present recent structural work that have identified the docking sites of several cardiotonic drugs on cardiac troponin C and discuss their relevance in the direction of troponin based drug design in the therapy of heart disease.